Coronavirus Era: Implications for Massive Open Online Courses in Basic Education Institutions in Kenya (London Journal of Research In Humanities and Social Sciences, 2022)
The Coronavirus (COVID 19) disease affected the global community at an alarming rate. The pandemic affected regular business globally. Despite the role schools play in raising learners' skills, they had to be closed. To mitigate the impact of COVID-19 on education, the education sector should focus on the role of MOOCs in basic education institutions. In Kenya, MOOCs have been adopted in institutions of higher learning. However, there is no evidence of information technology being implemented in basic education institutions. The study examined the impact of COVID-19 on education. It also assessed the role of information technology as a communication mode in mitigating the COVID-19 pandemic. Furthermore, the study discussed online initiatives that are crucial in mitigating the impact of the Coronavirus. The study was guided by e-learning theory as advanced by Richard E. Mayer, John Sweller, and Roxana Moreno in 2015. Mixed method approach was used in the study. A study sample of 384 was drawn to conform to the confidence interval of 0.05, a confidence level of 1.96, and a standard deviation of 0.5. Regression analysis was used to test hypothesis of the study. The study findings might be significant stakeholders for the actualization of e-learning in schools.
Keywords: structural semantics; translation studies; syntax; source language; target language; trends; eLearning; coronavirus; schooling